Occupational Safety and Health Behaviors among Agricultural Workers in Rural Area Indonesia - Muhammad Riswal; Mallapiang, Fatma; Andi Muhammad Multazam (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2021)
Background: Data from the Ministry of Health of the Republic of Indonesia (2016) showed that the highest prevalence of musculoskeletal disease in Indonesia by occupation is farmers. One of the areas where the majority of the population works as farmers is the To Bentong Tribe in Bulo-bulo Village, Barru Regency, South Sulawesi. To Bentong tribal farmers still farm and cultivate crops in the traditional way. Aim: In general, this study aims to determine how the behavior of Occupational Safety and Health (OSH) of To Bentong Tribe farmers in Bulo-Bulo Village, Barru Regency. In particular, this study aims to determine the use of PPE when farming, work postures and Musculoskeletal Disorders (MSDs) complaints experienced by farmers, as well as the pattern of seeking treatment by To Bentong Tribe farmers in Bulo-Bulo Village, Barru Regency. Method: This research design used a qualitative approach, where the method applied was the ethnographic method, while the data collection techniques used were observation, in-depth interviews, and documentation. Sources of information from this study consisted of main informants (6 persons as Bentong Tribe farmers) and key informant was Bentong Tribe Head, Bulo-Bulo Village Head, Bulo-Bulo Hamlet Head, and Bulo-Bulo Health Center Head). Result: Based on the results of research obtained through direct observation and in-depth interviews with all informants, it was found that the To Bentong Tribe farmers still lacked knowledge and understanding of Occupational Safety and Health (OSH). At the time of observation, the farmers preferred not to wear footwear. The farmers believe that the rituals performed can provide safety during work even if they do not use PPE (Personal Protection Equipment). In this study it was also found that the complaints most often felt by farmers related to work posture and feeling pain in the joints, hips, and back of the neck, as well as injuries caused by being hit by sharp objects such as iron from tractors, tools for cutting rice, and wood accidentally found in the rice fields. While the results of research related to the pattern of seeking treatment for the To Bentong Tribe farmers, farmers prefer traditional medicine to having to go to health services. This is because, traditional medicine is easier to obtain and can be processed quickly, the distance to health services is quite far, and the terrain that must be traveled can only be traversed by two-wheeled vehicles. Conclusion: Socialization to farmers is very important to increase knowledge about behavior and the application of occupational safety and health (OSH) in the agricultural sector.